2013
DOI: 10.1038/bjc.2013.521
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for endometrial cancers with suspected cervical involvement: is radical hysterectomy needed (a GOTIC study)?

Abstract: Background:Radical hysterectomy is recommended for endometrial adenocarcinoma patients with suspected gross cervical involvement. However, the efficacy of operative procedure has not been confirmed.Methods:The patients with endometrial adenocarcinoma who had suspected gross cervical involvement and underwent hysterectomy between 1995 and 2009 at seven institutions were retrospectively analysed (Gynecologic Oncology Trial and Investigation Consortium of North Kanto: GOTIC-005). Primary endpoint was overall surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 16 publications
4
43
1
5
Order By: Relevance
“…In addition, they also reported that perioperative and late adverse events were more common in patients treated with radical hysterectomy. 23 In the present study, we compared 51 patients who had radical hysterectomy, with 199 patients with simple hysterectomy. In our multivariate analysis, radical hysterectomy improved neither DFS nor OS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they also reported that perioperative and late adverse events were more common in patients treated with radical hysterectomy. 23 In the present study, we compared 51 patients who had radical hysterectomy, with 199 patients with simple hysterectomy. In our multivariate analysis, radical hysterectomy improved neither DFS nor OS.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study from Japan, radical surgery in stage II endometrial cancer did not result in any survival benefit compared with simple hysterectomy but was associated with more peri-operative and late adverse events 104. Another recent study found that parametrial spread cannot be predicted by cervical involvement alone but may be predicted by various lymphovascular space invasion (LVSI)-related histopathological factors 105.…”
Section: Surgerymentioning
confidence: 99%
“…104 Another recent study found that parametrial spread cannot be predicted by cervical involvement alone but may be predicted by various lymphovascular space invasion (LVSI)-related histopathological factors. 105 However, radical hysterectomy is considered in cases of obvious involvement of the parametrium.…”
Section: How Radical Should the Surgery Be In Different Stages And Pamentioning
confidence: 99%
“…Risk factors of PMI included depth of myometrial invasion, lymphovascular space invasion, and cervical involvement [2,3]; cervical involvement alone could not be a predictor of PMI [5]. Therefore, it is not clear whether parametrial resection is necessary for clinical stage I/II patients, particularly for patients with deep myometrial invasion or lymphovascular space invasion, and it is also undetermined if RH is needed for clinical stage II patients with cervical involvement [6]. …”
Section: Introductionmentioning
confidence: 99%